The application of Lean Manufacturing at PT XYZ Packaging Unit with the Value Stream Mapping (VSM) Approach - HarisTanti, Sindy Nindia Maretha; Mashudah Sabilaturrizqi; Mustika Ratnawati Faizzah; Puteri Nurul Ma’rifah (UNIPA PRESS, 2025)
The challenges of manufacturing companies in facing global market competition must be able to maintain the effectiveness and efficiency of operational processes that take place, including one strategy in getting good work productivity by focusing on eliminating waste that occurs in the operational process. In the packaging process, there are 14 activities classified into 9 operation activities, 3 transportation activities, 1 inspection activity and 1 storage activity. Of all these activities are categorized as 50% value added activity with a time percentage of 62%, non-value added activity neccessary activity of 36% with a time percentage of 29%, while 14% of activities as non-value added activity with 9% percentage of time. Improvements are made by adding a transfer conveyor from raw materials to the hopper, categorizing activities outside packaging as external activities, changing the number of operators and work schedules, eliminating activities with pallet investment. The impact of the improvement is by eliminating activities from 14 activities to 12 activities.